2006
DOI: 10.1111/j.1364-3703.2006.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensin over‐expression in Arabidopsis limits pathogen invasiveness

Abstract: SUMMARY The function of the cell wall protein extensin has been the subject of much speculation since it was first isolated over 40 years ago. In order to investigate the role of extensins in plant defence, we used the gain-of-function strategy to generate transgenic Arabidopsis plants over-expressing the EXT1 extensin gene. These were infected with the virulent bacterial pathogen Pseudomonas syringae DC3000 and symptom development was monitored. Lesions on the transgenics were on average five-fold smaller tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…The up-regulation of two extensin genes, which were categorized in the cell-wall-related category, is also consistent with a defense function. Extensins are, in fact, Hyp-rich glycoproteins that are hypothesized to form cross-linked networks that strengthen the plant cell wall, and so create a barrier to pathogen attack (Wei and Shirsat, 2006). A significant number of genes related to the production and neutralization of reactive oxygen species were found to be up-regulated in this study.…”
Section: Host Cellular Processes Affected By Cmm Infectionmentioning
confidence: 61%
“…The up-regulation of two extensin genes, which were categorized in the cell-wall-related category, is also consistent with a defense function. Extensins are, in fact, Hyp-rich glycoproteins that are hypothesized to form cross-linked networks that strengthen the plant cell wall, and so create a barrier to pathogen attack (Wei and Shirsat, 2006). A significant number of genes related to the production and neutralization of reactive oxygen species were found to be up-regulated in this study.…”
Section: Host Cellular Processes Affected By Cmm Infectionmentioning
confidence: 61%
“…The antimicrobial peptides SN1 and SN2 from potato and the cell wall-associated protein extensin have been previously implicated in resistance to bacterial diseases (Berrocal-Lobo et al 2002;Wei and Shirsat 2006;Almasia et al 2008). Using virus-induced gene Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Research on a number of host-pathogen systems has shown that extensin levels increase in response to pathogen ingress and proliferation (Davies et al 1997;Hauck et al 2003). One study convincingly demonstrated a functional linkage between extensin synthesis and plant resistance to pathogen attack (Wei and Shirsat 2006), as EXT1 over-expressing transgenic Arabidopsis were resistant to Pseudomonas syringae pv. tomato DC3000.…”
Section: Introductionmentioning
confidence: 99%
“…Both are structural components of plant cell walls and belong to the hydroxyproline-rich glycoprotein superfamily. Cross-linking of hydroxyproline-rich glycoproteins and glycosylation are key processes in the strengthening of the cell wall and contribute to plant resistance by limiting pathogen invasion (Wei and Shirsat, 2006). In addition, several other genes involved in the modification of polysaccharides were differentially regulated (AT4G25820, AT428850, AT5G5730).…”
Section: Expression Of Genes Related To the Cell Wallmentioning
confidence: 99%
“…The plant cell wall is a dynamic arrangement of proteins, sugars, and phenols with a substantial structural complexity that plays an essential role in plant defense (Hückelhoven et al, 1999;Wei and (E) Assessment of temperature via infrared light images in leaves of plants treated as described in (A) and exposed to Pst bacteria for 24 h. Shirsat, 2006;Hückelhoven, 2007;Deepak et al, 2010). Previously, we observed enhanced formation of papillae in barley plants pretreated with oxo-C14-HSL and challenged with the pathogenic fungus Blumeria graminis f sp hordei (Schikora et al, 2011).…”
Section: Oxo-c14-hsl Primes Plants For Cell Wall Reinforcementmentioning
confidence: 99%